Organization of justice and trial in Moldavia (the second half of the 18th century) - Chelcu, Catalina (Saeculum Christianum. Pismo Historyczne, 2019)
In our study we are concerned with the issue of the judicial organization and trial procedure, as well as the relation between common law and written law in Moldavia during the second half of the 18th century especially during the last quarter. During this period the legal system continued to be renewed in terms of criminal preoccupations. Both the princes of Moldavia and of Walachia focused on the reformation of justice. The fact that the princes succeeded each other on the throne in the Phanariot 18th century meant, from this standpoint, a great advantage, as different measures regarding the judicial organization and the procedure were promoted, by means of acts with similar content in Iași and in Bucharest. In this context, the prince preserves the prerogative of supreme judge of the country, as well as his place in relation to the boyars-judges. The preservation of legal attributions by the prince in his capacity of supreme instance is underlined in the new form of judicial organisation by the issuing of the definitive sentence, after having read the report including the boyars-judges’ proposition to punish the perpetrators. The motivation of the penalty also invoked extenuating or aggravating circumstance, which diminished or, on the contrary, increased the content of the penalty. The legal documents in Moldavia, dating from the second half of the 18th century, prove the presence of the Byzantine pravila in the legal theory and practice of that time. The Pravila [Law] meant therefore, as we could see in the contemporaries’ testimonies, the Byzantine written law, law guides made according to the Vasilika or the “Imperial law”, those legal texts in 60 volumes made in the 9th century at the demand of Leo VI (also called the Wise, 886-912), which represented an adaptation in Greek of the Roman Law, codified under the Byzantine emperor Justinian I (527-565). The foreign travellers in late 18th century Moldavia remind of the use of the Law of Harmenopoulos in trying criminal issues. Constantine Harmenopoulos was a judge in Thessaloniki, and his work’s title was Hexabiblos, in accordance with the six books it consisted of. This was made in 1345, summarising the Byzantine legislation included in the Vasilika and in the normative acts that had modified them by then, under the form of a guide. It was estimated that this work, and another legal guide, a nomocanon translated in Slavonic and used in the Romanian area starting with the 14th century, i.e. the Syntagma of Matthew Blastares of 1335, were created to replace the Vasilika, as they were “more concise and briefer for the needs of the trying courts”. It was considered that the Byzantine legal literature was very present in the judicial practice during the Phanariot rules, including in the form of those Vasilika (Fabrotus edition of 1647), as well as in other significant laws. But other such collections of nomocanons circulated in Moldavia as well. Particularly far-spread was Vaktiria ton Archiereôn (Bishop’s Staff), a work written by the monk Jacob of Ioannina, at the request of the Patriarch of Constantinople, Parthenius, and printed in 1645. It is also worth mentioning that – in the documentary sources preserved and researched thus far – the impact of sources where the Byzantine law texts constituted the legal grounds concerns mainly civil cases and, to a lesser extent, criminal cases. Border-related litigations – due to violating the protimisis right or to conflicts regarding the inheritance of lands or wealth in general – were solved in courts by consulting the Byzantine juridical standards. Most of the times, it is generically called the “holy code of law”. Hence, trial by “law code” became a reality from the second half of the 18th century, as proven by the documentary sources made available thus far.